Pengaruh Desain Pencahayaan Kelas terhadap Proses Belajar Mengajar di Universitas Matana - Leonardo Leonardo; Michelle Aprilia Wijaya (Prodi Arsitektur Universitas Matana, 2019)
There are several factors that influence the teaching and learning process in the classroom. These factors can be something that can be calculated (quantitative) or that cannot be seen (qualitatively). The teaching and learning process can be influenced by factors from inside and outside the classroom, which affect the activities of the teaching and learning process in the classroom. One of the factors that influence the teaching and learning process is lighting in the classroom. Good lighting in the classroom is in accordance with its standards both in number, position and quality of the lighting. In the teaching and learning process, lighting points and the number of appropriate light points are needed so as not to disturb teaching and learning activities. The purpose of class room lighting optimization is for students and instructors to do activities well in the classroom, efficiency in electricity consumption and comfort of vision. Is there a relationship between lighting in the classroom to the teaching and learning process in the classroom? Is there influence in class lighting on the teaching and learning process? This study uses a quantitative method to find out whether or not the influence is using SPSS version 16. Through this study, it is expected to provide knowledge about the effects of lighting on the teaching and learning process in the classroom. The results of this study indicate that the relationship between lighting and teaching and learning processes is moderate or not too strong and significant with r = 0.470 t = 3.727 between lighting in the classroom and the teaching and learning process. The effect of lighting in the classroom on the teaching and learning process is 22%.Keywords : lighting design, teaching and learning